2022
DOI: 10.1007/s40145-021-0559-x
|View full text |Cite
|
Sign up to set email alerts
|

Microwave synthesis of duplex α/β-SiAlON ceramic cutting inserts: Modifying m, n, z values, synthesis temperature, and excess Y2O3 synthesis additive

Abstract: Duplex α/β-SiAlON ceramic cutting inserts (30α:70β) were synthesized by microwave sintering. The effects of solid solution parameters (m, n, z), synthesis temperature, and amount of excess Y2O3 synthesis additive on phase assemblage, microstructure, mechanical properties, and cutting performance were systematically investigated. It was found that increasing m value could improve the formation of α phase while high z value over 1.0 resulted in the dissolution of α phase into β phase and intergranular phase. Inc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 45 publications
0
8
0
Order By: Relevance
“…Jack and Oyama reported that SiAlON is an electroneutral solid solution formed in the hot-pressing sintering process of Si3N4-Al2O3 [7,8]. Subsequent studies showed that SiAlON ceramics are mainly divided into α-and β-SiAlON based on the differences in the elements and solid solution morphologies [9,10]. The chemical formula of α-SiAlON is MxSi12-(m+n)Alm+nOnN16-n, and metal atoms (M) occupy cell gaps to maintain electricity charge equilibrium.…”
Section: Introductionmentioning
confidence: 99%
“…Jack and Oyama reported that SiAlON is an electroneutral solid solution formed in the hot-pressing sintering process of Si3N4-Al2O3 [7,8]. Subsequent studies showed that SiAlON ceramics are mainly divided into α-and β-SiAlON based on the differences in the elements and solid solution morphologies [9,10]. The chemical formula of α-SiAlON is MxSi12-(m+n)Alm+nOnN16-n, and metal atoms (M) occupy cell gaps to maintain electricity charge equilibrium.…”
Section: Introductionmentioning
confidence: 99%
“…Compositionally variable SiAlONs with a wide range of physical and mechanical properties possess advantages over their parent Si 3 N 4 and are achieved by substituting Al and O for Si and N in the SiAlON structure, respectively. [2][3][4][5] In this family, β-SiAlON has a typical chemical composition of Si 6−z Al z O z N 8−z , (where 0 < z < 4.2) and is an attractive phase exhibiting high strength, good thermal-shock resistance as well as oxidation resistance.…”
Section: Introductionmentioning
confidence: 99%
“…SiAlONs have a wide composition range and several crystal structures, (α, β, O, X, and AlN‐polytypoid phases) and are predominantly solid solutions formed in the quaternary Si 3 N 4 ‐Al 2 O 3 ‐AlN‐SiO 2 system. Compositionally variable SiAlONs with a wide range of physical and mechanical properties possess advantages over their parent Si 3 N 4 and are achieved by substituting Al and O for Si and N in the SiAlON structure, respectively 2–5 . In this family, β‐SiAlON has a typical chemical composition of Si 6− z Al z O z N 8− z , (where 0 < z < 4.2) and is an attractive phase exhibiting high strength, good thermal‐shock resistance as well as oxidation resistance.…”
Section: Introductionmentioning
confidence: 99%
“…Silicon nitride (Si 3 N 4 )‐based ceramics have been attracted much attention because of their wear resistance, corrosion resistance, oxidation resistance, excellent dielectric, and mechanical properties at room as well as elevated temperature environments 1–5 . It has become a potential material in high‐temperature and structural applications, wave‐transparent material such as gas engine parts, cutting tools, heat exchangers, bearings, orthopedic biomaterials, and so on 6–11 . However, Si 3 N 4 is not only a strong covalent compound but also its self‐diffusion coefficient, volume diffusion, and grain boundary diffusion rate during densification are small, so it is difficult to be densified by conventional solid‐state sintering 12 .…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4][5] It has become a potential material in high-temperature and structural applications, wave-transparent material such as gas engine parts, cutting tools, heat exchangers, bearings, orthopedic biomaterials, and so on. [6][7][8][9][10][11] However, Si 3 N 4 is not only a strong covalent compound but also its self-diffusion coefficient, volume diffusion, and grain boundary diffusion rate during densification are small, so it is difficult to be densified by conventional solid-state sintering. 12 Therefore, the introduction of additives for liquid phase sintering, pressureless sintering, hot-pressing (HP) sintering, gas pressure sintering, spark plasma sintering, and other new technologies to prepare dense Si 3 N 4 ceramics has become a hot research topic.…”
Section: Introductionmentioning
confidence: 99%